1998
DOI: 10.1080/01635589809514660
|View full text |Cite
|
Sign up to set email alerts
|

Slow‐release pellets of sodium butyrate increase apoptosis in the colon of rats treated with azoxymethane, without affecting aberrant crypt foci and colonic proliferation

Abstract: We investigated whether sodium butyrate, administered orally as gastroresistant slow-release pellets to rats, could affect markers of colon carcinogenesis. F344 male rats were fed a high-fat diet (230 g/kg corn oil, wt/wt) and treated with two injections (1 wk apart) of azoxymethane (15 mg/kg sc) or saline. Rats were then divided into two groups: one received the diet with 1.5% (wt/wt) sodium butyrate for 10 weeks to provide 150 mg butyrate/day, and one group received no butyrate. At the end of this period, ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 20 publications
2
16
0
1
Order By: Relevance
“…An inverse relationship between colon tumor mass and fecal butyrate levels was observed in rats, supporting this hypothesis (4,5). Caderni et al (6) provided evidence that oral administration of butyrate in the form of an entericresistant slow-release pellet significantly increases colonocyte apoptosis rate in a rat model of colon cancer, indicating a potential anticancer effect in vivo. We have recently shown that high butyrate levels, obtained after fermentation of soluble dietary fibers, or rectally instilled, inhibits early and late events in colon tumorigenesis by controlling the transcription, expression and activity of key proteins involved in the apoptotic cascade.…”
supporting
confidence: 52%
“…An inverse relationship between colon tumor mass and fecal butyrate levels was observed in rats, supporting this hypothesis (4,5). Caderni et al (6) provided evidence that oral administration of butyrate in the form of an entericresistant slow-release pellet significantly increases colonocyte apoptosis rate in a rat model of colon cancer, indicating a potential anticancer effect in vivo. We have recently shown that high butyrate levels, obtained after fermentation of soluble dietary fibers, or rectally instilled, inhibits early and late events in colon tumorigenesis by controlling the transcription, expression and activity of key proteins involved in the apoptotic cascade.…”
supporting
confidence: 52%
“…Indeed, the effect of butyrate on the proliferation of normal colon cells is still under discussion. While butyrate may be essential for restoring proliferation in different pathologies (ulcerative colitis, parenteral nutrition, etc), 6,40 physiological levels of butyrate induced either by feeding wheat bran 41 or by pellets 42 did not alter the proliferation of normal cells. In addition, the variations in the number of cells containing either neutral, acidic or sulphated mucins, different in the proximal or distal colon, may re¯ect local variations in pH, lactic acid, acetate and butyrate between these two anatomical sites.…”
Section: Discussionmentioning
confidence: 95%
“…Although TB and BA inhibited cell proliferation in some studies, apoptosis induction has been suggested as their main chemopreventive mechanism 12,[37][38][39] and was shown to occur specifically in transformed tissues. 40 In our study TB induced apoptosis, but did not inhibit cell proliferation.…”
Section: Discussionmentioning
confidence: 99%